2017
DOI: 10.1016/j.jviromet.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

HIV drug resistance testing among patients failing second line antiretroviral therapy. Comparison of in-house and commercial sequencing

Abstract: Introduction HIV genotyping is often unavailable in low and middle-income countries due to infrastructure requirements and cost. We compared genotype resistance testing in patients with virologic failure, by amplification of HIV pol gene, followed by “in-house” sequencing and commercial sequencing. Methods Remnant plasma samples from adults and children failing second-line ART were amplified and sequenced using in-house and commercial di-deoxysequencing, and analyzed in Harare, Zimbabwe and at Stanford, U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This has been proven to be cost-effective in high-income countries (14) but practically limited and not feasible in many LMICs, as it remains complex and costly (15,16). In Zimbabwe, although a validation of an in-house genotyping method at the African Institute for Biomedical Sciences and Technology laboratory showed good-quality HIVDR results, Chimukangara et al concluded that the implementation of such techniques in Zimbabwe was too costly (17). Additionally, Phillips et al showed that the use of GRT at the time of first-line-ART failure as part of the decision whether to switch to second-line therapy was not cost-effective in LMICs (16).…”
mentioning
confidence: 99%
“…This has been proven to be cost-effective in high-income countries (14) but practically limited and not feasible in many LMICs, as it remains complex and costly (15,16). In Zimbabwe, although a validation of an in-house genotyping method at the African Institute for Biomedical Sciences and Technology laboratory showed good-quality HIVDR results, Chimukangara et al concluded that the implementation of such techniques in Zimbabwe was too costly (17). Additionally, Phillips et al showed that the use of GRT at the time of first-line-ART failure as part of the decision whether to switch to second-line therapy was not cost-effective in LMICs (16).…”
mentioning
confidence: 99%